Bigo Live Wajah Baru Cybersex: Lemahnya Penegakan UU Pornografi - Kusuma, Rafles Abdi; Satria, Sigit (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2019)
This article discusses about the development of information and communication technology in broadcasting in the digital era. Today the development of the internet raises new ways of broadcasting (boardcasting) carried out by ordinary citizens. Livecasting is a contemporary way to make anyone appear realtime in front of the camera. Some of the livecasting features that people use are live facebook, and bigo live. This article focuses on the Bigo Live feature which offers chat features with realtime audio and video support. Bigo live at the beginning of the appearance of a lot of pornographic content in it. So the author argues that Bigo is the new face of CyberSex carried out by ordinary users who are not commercial sex workers. The author tries to examine from the perspective of the development of cell phones and new cultures from the use of cellular phones in the digital era. For example features the gift of diamond coins purchased from real money and given to